2018
DOI: 10.20452/pamw.4347
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bronchitis symptoms in subjects without chronic obstructive pulmonary disease: prevalence, burden and risk factors in southern Poland

Abstract: INTRODUCTION Chronic cough and sputum production are among the most commonly reported medical symptoms. 1 Cough and sputum expectoration for most days for at least 3 months during at least 2 consecutive years are considered the epidemiological criteria of chronic bronchitis (CB). 2 Clinical diagnosis requires exclusion of common diseases causing CB symptoms, especially asthma and heart failure. CB was originally recognized as a stand-alone condition, 3 but since the term chronic obstructive pulmonary disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…CB is also an age-related disease that is common in elderly individuals. Most studies showed that individuals aged over 50 or 65 years had a greater risk of CB 10,11,27,[37][38][39] and our results were consistent with those of previous studies. Lung function gradually declines after 35 years of age, manifested by the progressive loss of alveolar surface area, dilation of air spaces, reduced mucociliary clearance, and changes in elasticity 40 .…”
Section: Discussionsupporting
confidence: 93%
“…CB is also an age-related disease that is common in elderly individuals. Most studies showed that individuals aged over 50 or 65 years had a greater risk of CB 10,11,27,[37][38][39] and our results were consistent with those of previous studies. Lung function gradually declines after 35 years of age, manifested by the progressive loss of alveolar surface area, dilation of air spaces, reduced mucociliary clearance, and changes in elasticity 40 .…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of CB symptoms in individuals aged 40 years or older ranges from 3% to 22% [ 6 , 10 , 11 ]; the variability is due in part to the geographical location [ 6 ] or living in rural areas [ 7 ]. The prevalence of CB increases among smokers (38% in our study had CB) and with the presence of COPD (45% of our COPD population had CB, whereas only 27% of the noCOPD had it), in line with previous reports [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is the most important known risk factor for the development of chronic bronchitis, however CB is also common in the general population, with prevalence estimates varying widely from 3 to 22% of non-smoking adults, variability due in part to geographical location [ 6 , 10 , 11 ]. Occupational and biomass exposures, air pollution, long-term exposure to multiple inhaled smokes vapors and particles, asthma, allergies, and bronchiectasis are some of the known factors contributing to the development of chronic bronchitis in the general population [ 12 ].…”
Section: Introductionmentioning
confidence: 99%